Exploring the Medico-legal death scene investigation of sudden unexpected death of infants admitted to Salt River mortuary, Cape Town, South Africa - Bennett, Tracy (Department of Clinical Laboratory Science, 2019)
A death scene investigation (DSI) forms an integral part of the inquiry into death, particularly for sudden unexpected death of infants (SUDI). Global guidelines exist for DSI, however, it is unclear how many countries adhere to them, and to what extent they are followed. Therefore, a systematic literature review was undertaken to assess the scope of SUDI DSI performed internationally. It was found that national protocols have been established in some countries, and have shown value in guiding medico-legal examinations. Further, South Africa did not routinely perform DSI for SUDI cases, nor was there a protocol. This was largely attributed to the burden of SUDI cases as well as the lack of resources. Therefore, this study aimed to suggest realistic and feasible ways to improve DSI for local SUDI cases. This research study consisted of three phases: 1) A twoyear review of medico-legal case files from SUDI cases investigated at Salt River Mortuary; 2) The prospective observation of DSI for ten SUDI cases, using a semi-structured checklist; and 3) he distribution and analysis of a survey regarding SUDI DSI to all registered, qualified forensic pathologists in South Africa. The results showed that the SUDI death scenes were assessed in 59.2% of cases at Salt River Mortuary, with inconsistent levels of documentation or photography. Death scenes were never investigated in cases where the infant was pronounced dead on arrival at a medical facility. In both scene observations (n=10) and retrospective analysis (n=454) only one case incorporated a re-enactment, but the majority of infants were moved prior to DSI. The findings support the need for a standardised approach to DSI, coupled with specialised training for staff. Based on the available resources, this should focus on the establishment of guidelines pertaining to photography, handling medicine and scene reconstruction, as well as accurate use of relevant documentation.